Vascular endothelial growth factor C as a predictive factor in cervical cancer? - Biedka, Marta; Makarewicz, Roman; Lebioda, Andrzej; Kardymowicz, Hanna; Goralewska, Alina (Contemporary Oncology/Współczesna Onkologia, 2010)
Background: It is tempting to suggest that cervical cancer is one of the most common malignancies in a woman’s life. Its prognostic factors are: tumour stage, lymph node status, histological type, and level of haemoglobin. Angiogenesis, which is the formation of a new blood vessel from the existing vascular network, is essential for tumour growth, progression and metastasis. Vascular endothelial growth factor (VEGF) has been identified as one of the most important factors of angiogenesis. VEGF-C, a novel member of the family, is a relatively specific lymphangiogenic growth factor. However, little is known about the prognostic and/or predictive significance of angiogenesis in cervical cancer. Aim of the study: This prospective study will attempt to evaluate serum VEGF-C in cervical cancer and its correlation with clinicopathological features. Material and methods: Blood samples were collected from 27 patients affected by FIGO I-IV stage cervical cancer, who were admitted to the Department of Oncology and Brachytherapy, Collegium Medicum of Bydgoszcz Nicolaus Copernicus University. Serum VEGF-C concentration was determined by means of a quantitative sandwich enzyme immunoassay (ELISA). All data were assessed with the statistical analysis program Statistica. Results: The median serum VEGF-C was 72.65 pg/ml. Serum VEGF-C levels measured in patients were associated with primary tumour size. Serum VEGF-C was not correlated with tumour stage or other clinicopathological parameters. Conclusion: In conclusion, our study suggested that serum VEGF-C plays an important role in tumour growth and progression in cervical cancer. Nonetheless, further studies are essential to explore the underlying mechanism.